Novel iron-rich mullite solid solution synthesis using fused-silica and α-Al2O3 powders. Issue 4 (March 2019) - Ye, Hang; Li, Yong; Sun, Jialin; Sun, Yang; Wu, Xiaofang; Yan, Mingwei
Abstract: An iron-rich mullite solid solution was synthesized by using α-Al2 O3, fused-silica and Fe2 O3 powders at elevated temperatures. The phase compositions and microstructures of the synthesized samples were characterized by X-ray diffraction (XRD), energy dispersive spectrometer (EDS) and field emission scanning electron microscope (FESEM). The occurrence states of Fe 2+ and Fe 3+ at different temperatures were analysed by X-ray photoelectron spectroscopy (XPS). The influence and the reaction mechanism of Fe2 O3 addition on the synthesis of the mullite solid solution were clarified. The results showed that with the addition of Fe2 O3, a liquid-solid sintered state was formed at 1300–1400 °C, which leaded to a reduction in the mullitization temperature. After sintering at 1600 °C, the quantitative analysis showed that the mullite phase content was 100%. Meanwhile, the Fe 3+/2+ ions entered completely into the mullite to form a stable solid solution, which exhibited the crystal morphology of a spherical shape and a short columnar shape with a low aspect ratio. The crystal grains were interwoven and squeezed each other, showing good structural stability. The refractoriness under load (RUL) property of the sample sintered at 1700 °C was slightly higher than that of the sample sintered at 1600 °C.